Insider Trading and Law Enforcement in the Capital Market - Tara Dewi Niandita (Riviera Publishing, 2024)
Illegal stock trading, or insider trading, has become a significant issue in the capital markets, both in Indonesia and the United States. This research aims to compare law enforcement related to insider trading between the two countries. This research uses a normative method with legislative and conceptual approaches. Data was collected through analysis of laws and regulations and case studies related to insider trading practices. The findings show that the regulations in the UUPM in Indonesia still use the fiduciary duty theory, which limits the scope of actions that can be sanctioned. In contrast, in the United States, the application of the fiduciary duty theory and misappropriation theory provides stronger legal protection and stricter sanctions against insider trading offenses. Although both countries have regulations prohibiting insider trading, the enforcement mechanism in the US is more comprehensive than in Indonesia. In the US, there are more legal precedents that clarify limits and sanctions, while in Indonesia, there is still a lack of implementation and understanding of insider trading. Enforcement of insider trading laws in the US is more effective than in Indonesia. The UUPM in Indonesia needs to be revised to integrate the misappropriation theory and strengthen sanctions against insider trading violations, in order to provide better protection to investors.